2019
DOI: 10.1371/journal.pone.0218469
|View full text |Cite
|
Sign up to set email alerts
|

Attention deficit hyperactivity disorder and future alcohol outcomes: Examining the roles of coping and enhancement drinking motives among young men

Abstract: Objective Although there is evidence that Attention Deficit Hyperactivity Disorder (ADHD) symptoms are positively related to alcohol use and related problems among young adults, little research has examined the mechanisms that might explain this association. In response, this study examined the mediating effects of coping and enhancement drinking motives on the prospective associations between ADHD symptoms and alcohol outcomes. Method Participants ( N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 67 publications
4
14
0
1
Order By: Relevance
“…Fischer et al (2012) states that, even in the context of late-life cognitive disorders, memory clinics may not adequately identify and address ADHD. According to Faraone et al (2006), differentiating ADHD from other clinical disorders is often the most difficult part of making an ADHD diagnosis in adults, given the high comorbidity between ADHD and other psychiatric disorders such as major depressive and anxiety disorders (Paek et al 2016), internet addiction (Bielefeld et al 2017;Wang et al 2017), bipolar disorder (Klassen et al 2010;Mucci et al 2019), borderline personality disorder (Xenaki and Pehlivanidis 2015), substance abuse (Fatseas et al 2012), gambling disorders (Marmet et al 2018), or alcohol abuse (Grazioli et al 2019). Ginsberg et al (2014) remark that adults with ADHD are more likely to seek psychiatric services to obtain treatment for their other comorbid disorders than for ADHD, which adds more confusion and challenge for the clinicians that may fail to properly identify and distinguish ADHD symptoms from symptoms of the other comorbidities that appear as the primary reason for consultation.…”
Section: Introductionmentioning
confidence: 99%
“…Fischer et al (2012) states that, even in the context of late-life cognitive disorders, memory clinics may not adequately identify and address ADHD. According to Faraone et al (2006), differentiating ADHD from other clinical disorders is often the most difficult part of making an ADHD diagnosis in adults, given the high comorbidity between ADHD and other psychiatric disorders such as major depressive and anxiety disorders (Paek et al 2016), internet addiction (Bielefeld et al 2017;Wang et al 2017), bipolar disorder (Klassen et al 2010;Mucci et al 2019), borderline personality disorder (Xenaki and Pehlivanidis 2015), substance abuse (Fatseas et al 2012), gambling disorders (Marmet et al 2018), or alcohol abuse (Grazioli et al 2019). Ginsberg et al (2014) remark that adults with ADHD are more likely to seek psychiatric services to obtain treatment for their other comorbid disorders than for ADHD, which adds more confusion and challenge for the clinicians that may fail to properly identify and distinguish ADHD symptoms from symptoms of the other comorbidities that appear as the primary reason for consultation.…”
Section: Introductionmentioning
confidence: 99%
“…ADHD can have an impact on a student’s academic and social performance due to difficulties in maintaining attention, failure to complete tasks, forgetfulness, and excessive non-goal directed physical activities [ 14 ]. Moreover, the problem is not limited to in childhood period, it has also an impact on their mental health condition and social wellbeing in adulthood [ 15 ], which could be associated with having few or no friends, exercising antisocial behaviors, manifested depressive symptoms, exposed to stress, unable to stick in specific occupations/work, having poor social relationships, using a substance (like alcohol and smoking), exposing unplanned pregnancy, and experiencing multiple car accidents [ 16 21 ]. However, since the problem is highly neglected, a majority of children with ADHD remain undiagnosed or do not receive appropriate specialist services in high spite of morbidity [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that ADHD itself might be correlated with AUD [ 12 , 13 ]. Previous longitudinal studies have shown that ADHD might have a significant impact on alcohol-related behaviors [ 13 , 14 ]. The high levels of impulsivity and sensation seeking that has been described among individuals with ADHD may significantly increase the risk of AUD [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high levels of impulsivity and sensation seeking that has been described among individuals with ADHD may significantly increase the risk of AUD [ 15 ]. In addition, prospective data highlighted that both the attenuation of negative affect and the enhancement of positive mood or wellbeing, might represent possible clinical mediators of the association between ADHD and AUD [ 14 ]. Moreover, observational studies have shown higher rates of problematic alcohol use in adults suffering from ADHD, with genetic links primarily underlying this association [ 16 ].…”
Section: Introductionmentioning
confidence: 99%